Hubungan Pengetahuan Dengan Tingkat Kepatuhan Minum Obat Pada Penderita Diabetes Mellitus Di Wilayah Kerja Puskesmas Kecamatan Slahung - Putri Ayu Kusuma Wardhani; Lina Ema Purwanti; Dianita Rifqia Putri; Hery Ernawati; Elmie Muftiana (Universitas Muhammadiyah Ponorogo, 2023)
Diabetes Melltitus makes Indonesia ranked as the third highest case in the world. In addition, this disease has caused the Puskesmas working area of Slahung District to be the third highest after Sawoo and Ngrayun Districts. This condition is certainly a special concern, especially in an effort to control blood glucose levels, one of which is by taking medication. In the activity of drug consumption, it is also influenced by aspects, one of which is obedience. This study aims to analyze the correlation between patient knowledge and adherence to taking antidiabetic drugs at the Puskesmas in the Slahung Subdistrict work area.Quantitative analytics became the design of this study which was carried out on 99 samples of purposive sampling. Furthermore, the data were analyzed using univariate and bivariate analysts. The results explained that the knowledge level of the majority of patients was sufficient, namely as many as 50 respondents (50.5%). Meanwhile, the adherence rate of taking antidiabetic drugs is a moderate category, namely 60 people (60.6%). Thus, there is a significant relationship with the p value of 0.020 α 0.05.